European Handbook of Dermatological Treatments 2015
DOI: 10.1007/978-3-662-45139-7_87
|View full text |Cite
|
Sign up to set email alerts
|

Seborrheic Dermatitis

Abstract: Seborrheic dermatitis is a chronic recurrent infl ammatory skin disorder frequently occurring in infancy and adulthood. It clinically presents with sharply demarcated erythematous papules, patches, and plaques with greasy scales primarily affecting areas of high sebaceous gland activity, namely, the scalp, face, upper chest, upper back, and fl exures. Itching can be present. The estimated prevalence of adult seborrheic dermatitis is 3-5 %, with a predilection in men. It has two incidence peaks, the fi rst in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cannabinoids have demonstrated anti-inflammatory and antipruritic properties, highlighting a potential therapeutic role [ 7 ]. The mechanisms by which cannabinoids decrease inflammation and pruritus are diverse and involve CB1/CB2 receptors, chemokines, and an interaction between the endocannabinoid system and the immune system [ 7 , 124 ]. Nam et al showed that a CB1 agonist ameliorates AD in mouse models possibly by decreasing mast cell proliferation [ 121 ].…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabinoids have demonstrated anti-inflammatory and antipruritic properties, highlighting a potential therapeutic role [ 7 ]. The mechanisms by which cannabinoids decrease inflammation and pruritus are diverse and involve CB1/CB2 receptors, chemokines, and an interaction between the endocannabinoid system and the immune system [ 7 , 124 ]. Nam et al showed that a CB1 agonist ameliorates AD in mouse models possibly by decreasing mast cell proliferation [ 121 ].…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
“…In a study with pediatric and adult subjects, a cream containing palmitoylethanolamide (PEA) significantly increased the mean time to the next eruption [ 123 ]. Similarly, in a pilot study, the use of a topical cannabinoid emulsion resulted in clinical resolution and prevented the relapse of mild atopic dermatitis in 80% of patients [ 124 ]. In another study, a cream containing PEA improved itching severity and sleep quality by an average of 60% among subjects [ 125 ].…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
See 1 more Smart Citation